Presence of herpesviruses in adenoid tissues of children with adenoid hypertrophy and chronic adenoiditis. - Karlida?, Turgut; Bulut, Yasemin; Keleş, Erol; Alpay, Hayrettin Cengiz; Seyrek, Adnan; Orhan, Israfil; Kaygusuz, Irfan (My University, 2012)
The aim of study was to determine the presence of some of the herpesviruses including herpes simplex virus (HSV), Epstein-Barr virus (EBV), and cytomegalovirus (CMV) in adenoid tissues of children with adenoid hypertrophy (AH) and chronic adenoiditis (CA) and to investigate the potential role of the herpesviruses in patogenesis of AH and CA. A total of 72 patients (41 boys, 31 girls; mean age 4 years and 2 months; range 2 to 9 years) who underwent adenoidectomy or adenotonsillectomy (with or without placement of a ventilation tube) in our clinic between October 2007 and May 2008, were included. The patients were divided into two groups, as AH group (n=42) and the CA group (n=30). Adenoid tissues collected from patients in both groups were analyzed by polymerase chain reaction (PCR) for the presence of HSV, EBV and CMV-DNA. The results of the PCR indicated that 33.3% in the AH group and 36.6% in the CA group were herpesvirus DNA positive. Among the herpesviruses studied, HSV-DNA was detected at the highest level (14.2% and 16.6%, respectively) in both groups, although the difference between the groups was not significant. EBV-DNA positiveness was 11.9% and CMV-DNA was 4.7% in the AH group, whereas, EBV-DNA positiveness was 13.3% and CMV-DNA was 6.6% in the CA group. Herpesviruses were determined at a high rate in adenoid tissue of children with AH and CA, suggesting that there may be a potential relationship between the presence of herpesviruses and occurrence of AH and CA in children. However, more extensive studies are required to elucidate the role of herpesviruses in the pathogenesis of AH or CA.
Keywords: Adenoidectomy; Adenoids; Child; Child, Preschool; Chronic Disease; Cytomegalovirus; DNA, Viral; Female; Herpesviridae Infections; Herpesvirus 4, Human; Humans; Hypertrophy; Male; Middle Ear Ventilation; Polymerase Chain Reaction; Simplexvirus; Tonsillectomy; Tonsillitis; virus DNA; adenoid; adenoidectomy; article; child; chronic disease; Cytomegalovirus; Epstein Barr virus; female; genetics; herpes virus infection; human; hypertrophy; isolation and purification; male; middle ear ventilation; pathology; polymerase chain reaction; preschool child; Simplexvirus; tonsillectomy; tonsillitis; virology